Does a Change of Government Influence Compliance with International Agreements? Empirical Evidence for the NATO Two Percent Target - Johannes Blum; Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
We examine whether changes of government influence compliance with international agreements. We investigate compliance with the NATO two percent target to which all NATO countries committed themselves during the NATO summit in Wales in 2014. The dataset includes the military expenditure by NATO countries over the period 2010–2018. The results suggest that countries that do not (yet) comply with the two percent target have smaller growth rates in military expenditure relative to GDP when they experienced a large change of government, e.g. a change from a rightwing to a leftwing government, than countries that did not experience such a large change of government since the NATO summit in 2014. Countries that experienced a large change of government are, thus, less likely to comply with the two percent target. Future research should examine the credibility problem of national governments in other international agreements too.
Keywords: D72; D74; H41; H56; P16; 330; International agreements; compliance; credibility; time inconsistency; change of government; military expenditure; two percent target; NATO; burden sharing